Cutting orientations of non-complex part in 4th axis CNC machining for rapid manufacturing process - Siti Norhanani, Saari (2017)
Considering time frame and cost needed while producing the parts or product affecting the production and customer satisfaction. Rapid Manufacturing can be adapted by using Computer Numerical Controlled (CNC) which is one of the methods in manufacturing. The tool accessibility can be increasing using 3-axis CNC milling machine with an indexing device and can overcomes most of the process constraints. While make an operation to finding the optimum cutting orientations, more work is required to create one by on~ orientation with the value of cutting orientation needed. So, need to make GUI to ensure the values of orientations key in are easy to make an operation. This thesis focuses on finding the optimum cutting orientation and to analyse the implication of orientation towards machining time. With making interface, the operation time can be reduced and easy to find the optimum cutting operation. RM is closely related with time but surely need to consider customer satisfaction. In analyses the implication of orientation towards machining time. Every orientation will give effect to the machining time which depends on the geometry of the models developed.